2012
DOI: 10.1111/j.1469-7998.2012.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social system on allosuckling and adoption in zebras

Abstract: Although nursing non‐filial offspring (allonursing) represents costly behaviour to the female, it occurs in a variety of taxa, including ungulates. The only three currently existing species of zebra differ in their ecology and social system. In the wild, mountain zebra Equus zebra and Grevy's zebra Equus grevyi live in arid environments, while plains zebra Equus quagga inhabit savannahs. Mountain and plains zebra mares form long‐term stable herds associated with a social hierarchy, whereas Grevy's zebra mares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Breeding and immunity are both expensive and somewhat incompatible, as elevations of one often compromise the other [ 82 ]. However, despite the fact that lactation and estrus behaviors are also very energetically costly [ 83 ], both lactation and FPM significantly predicted higher neutrophil counts in zebras; this may reflect an inflammatory response to the potentially injurious activities against mares of suckling young and mating stallions.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding and immunity are both expensive and somewhat incompatible, as elevations of one often compromise the other [ 82 ]. However, despite the fact that lactation and estrus behaviors are also very energetically costly [ 83 ], both lactation and FPM significantly predicted higher neutrophil counts in zebras; this may reflect an inflammatory response to the potentially injurious activities against mares of suckling young and mating stallions.…”
Section: Discussionmentioning
confidence: 99%
“…The youngest calves in the herd were never seen allosucking, despite of the fact that they had the possibility to do it just after joining the herd where other nursing female was present. In other ungulates, except in zebra [33], allosuckling was reported from the first day [4] or the first weeks [11], [20] of the calves' lives. Even calves with the large percentage extent of allosuckling (up to 100%, Table 2) allosucked only occasionally, being weaned by their mothers and using the opportunity to get surplus milk.…”
Section: Discussionmentioning
confidence: 99%
“…As the gap between the start of sucking and milk let-down is not documented in camels, we consider all bouts longer than 5 seconds as successful as in other studied species e.g. [4], [32], [33]. Sucking bout was considered to terminate when it was interrupted for at least 10 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, we revealed higher incidence of allonursing in Grévy's zebra than in plains and mountain zebra, where allonursing was associated with adoption (Olléová, Pluháček & King, ). We suggested that higher tolerance towards non‐filial offspring, including the occurrence of allosuckling in Grévy's zebras, could be affected by different social systems of zebra species as reported in several species of ungulates, rodents and primates (McGuire & Novak, ; Maestripieri, 1994 b ; Ekvall, ; Das, Redbo & Wiktorsson, ; Landete‐Castillejos et al ., ; McGuire et al ., ).…”
Section: Introductionmentioning
confidence: 77%